PENGARUH KOMPETENSI , DISPLIN KERJA TERHADAP KINERJA DIMEDIASI KOMITMEN ORGANISASIONAL (Pada SMP Negeri Di Kabupaten Pati) - Suparman, Suparman (Students Journal of Economic and Management, 2012)
The purpose of this research was to examine the influence ofTeachersâ competence and Discipline toward Performance with Organizational commitment as mediation (Study at Secondary Schools Teachers in Pati Regency). The population in this research is all Junior High School Teachers of Civil Servants (PNS) inÂ Pati regency. Sample method applies Stratified Proportional Random Sampling using Slovin. The data are collected from 206 respondents by using sampling method.The instrument which is used in this research is computer software SPSS ver.16. program. Method of analyses to used linier regression analyses by conducting test of classic assumption and 5 hypothesis. The results of this research showed that the variables of Teacher Competency has a positive influence on Organizational Commitment, Discipline teachers have a positive effect on organizational commitment, competence of teachers has a positive influence on the performance of teachers, discipline has a positive impact on teacher performance, organizational commitment has a positive influence on the performance of teachers. And as a mediation, commitment organizational canât be proved. It shows that commitment organizational canâtÂ mediate the influence of both competence and discipline toward teachersâ performance of junior high school teachers in Pati regency. Keywords: Teacher competence, discipline, Organizational Commitment, performanceÂ teacher